Elementary Students' Difficulties in Adding Fractions: A Computational Thinking Analysis - Halimah Nur Agustin; Neni Mariana; Tatag Yuli Eko Siswono; Wiryanto (Papanda Publisher, 2026)
This study analyzes elementary students’ difficulties in understanding fraction addition through the framework of computational thinking (CT). Fractions are widely recognized as one of the most challenging mathematical concepts for young learners due to their abstract nature and multiple representations. The purpose of this study is to identify students’ specific difficulties across the four CT dimensions; decomposition, pattern recognition, abstraction, and algorithmic thinking in the context of fractional addition. The research employed a qualitative descriptive design involving 19 sixth-grade students from an elementary school in Mojokerto, Indonesia. Data were collected through classroom observations, diagnostic tests, and semi-structured interviews. Findings show that 78.9% of students struggled with abstraction, 73.7% with decomposition, 68.4% with algorithmic thinking, and 63.2% with pattern recognition. Students frequently applied whole-number reasoning, failed to identify equivalence patterns, and were unable to construct systematic solution procedures. These results indicate that students’ difficulties are multidimensional and stem from insufficient scaffolding in linking conceptual understanding with procedural fluency. The study suggests that CT-based instructional strategies can strengthen students’ structural reasoning and support deeper learning of fraction concepts.